Divine Epithets of Lusitania - Beltrán Ortega, Alejandro (ARYS. Antigüedad: Religiones y Sociedades, 2021)
Roman Lusitania has always been considered a peripheral territory, in which pre-Roman traditions were active and in which most of its territory was formed as a rural space. These hypotheses were also transferred to the religious world, assuming that the Lusitanian religious reality consisted of a marked traditional character, with a massive presence of indigenous divinities. However, the detailed analysis allows us to see that Lusitania is not alien to the religious currents present in the rest of Hispania and by extension, in the rest of the Empire, and more specifically through the analysis of the use of divine epithets, whose use does not differ too much with the rest of the territories, as can be seen throughout the text